60 ans de peinture soviétique. - Davydova, M.V.; Diehl, Gaston; Elisseeff, V. (Paris : Galeries Nationales du Grand Palais, 1977)
Arkhipov, Abraham ; Bogorodsky, Fédor ; Chagall, Marc ; Deïneka, Alexandre ; Ioganson, Boris ; Kandinsky, Wassily ; Kontchalovsky, Pierre ; Kouprine, Alexanre ; Kouznetsov, Paul ; Lentoulov, Aristarkh ; Machkov, Ilya ; Malevich, Kasimir ; Nesterov, Michel ; Osmerkine, Alexandre ; Oudaltsova, Nadejda ; Petrov-Vodkine, Kouzma ; Rojdestvensky, Vassili ; Rylov, Arcadi ; Samokhvalov, Alexandre ; Sarian, Maritros ; Viliams, Pierre ; Volkov, Alexandre ; Brodsky, Isaac ; Grekov, Mitrophan ; Krymov, Nicolas ; Pimenov, Iouri ; Falk, Robert ; Korine, Paul ; Mechkov, Vassili ; Plastov, Arkadi ; Romadine, Nicolas ; Tchouikov, Simon ; Abegian, Mger ; Akynbekov, Mels ; Andronov, Nicolas ; Avetissian, Minas ; Bakhloul-Zade, Sattar ; Berzinch, Boris ; Chtranikh, Vladimir ; Dantzig, Maï ; Djaparidze, Outcha ; Djiaoukchtas, Silvastras ; Djoumabaev, Balek ; Endzelina, Livia ; Frenz, Vladimir ; Gromyko, Victor ; Iakovlev, André ; Iltner, Edgar ; Ivanov, Michel ; Ivanov, Victor ; Kalnynch, Edouard ; Klytchev, Izzat ; Korjev, Guelii ; Kormachov, Nicolas ; Kotska, André ; Malouev, Boris ; Mirzachvili, T.R. ; Moissenko, Evsei ; Mouradian, Sarkis ; Mylnikov, André ; Myznikov, Guenadii ; Nalbandian, Dmitri ; Narimanbekov, Togroul ; Nikitch, Anatole ; Nikonov, Paul ; Nisski, Georges ; Okorokov, Boris ; Ozol, Vilis ; Popkov, Victor ; Salakhov, Tair ; Savitskas, Augustinas ; Savitsky, Michel ; Smoline, Alexandre ; Smoline, Pierre ; Soubbi, Olev ; Soumarev, Vassilii ; Svechnikov, Dimitri ; Tabaka, Maïa-Nora ; Tchouikov, Simon ; Tioulenev, Vitaly ; Tkatchev, Serge ; Tkatchev, Alexis ; Toutounov, André ; Vachtchenko, Gabriel ; Yablonskaia, Tatiana ; Zagonek, Viatcheslav ; Zarinch, Indoulis ; Zaripov, Ildar ; Zvekhov, Efrem
biografie
Frans
boek
Keywords: Rusland